Cucurbituril‐Based Biomacromolecular Assemblies. Issue 8 (23rd December 2020) - Liu, Yao‐Hua; Zhang, Ying‐Ming; Yu, Hua‐Jiang; Liu, Yu
Abstract: The construction of controlled biomacromolecular assemblies has become a thriving area of supramolecular chemistry. In this context, cucurbiturils (CBs), a class of macrocyclic receptors having robust skeletons, hydrophobic cavities, and carbonyl‐laced portals, have been drawn into the limelight because of their advantageous molecular recognition characteristics with a variety of biomacromolecules, including peptides, nucleic acids, and proteins. In this minireview, we focus on the impressive advances in CB‐based biomacromolecular assemblies, such as in biosensors and assays, the regulation of biochemical reactions, and the treatment of serious diseases. CB‐promoted subcellular bioimaging has also been demonstrated in different organelles. The case studies presented herein demonstrate the numerous applications, from fundamental research to translational applications, of diverse CB‐based supra/biomacromolecular architectures. Abstract : This minireview highlights the recent progress in and emerging applications of cucurbituril‐based biomacromolecular assemblies with peptides, nucleic acids, and proteins. This rapidly developing area involves precise control over intermolecular communication at multidimensional levels and holds great promise for the creation of innovative biomaterials and therapeutic methods.